Conditional Knockout of Pdha1 in Mouse Hippocampus Impairs Cognitive Function: The Possible Involvement of Lactate - Chen, Wanxin; Sun, Xiaoxia; Zhan, Libin; Zhou, Wen; Bi, Tingting (Frontiers in Neuroscience, 2021)
Background and Purpose: Neurodegenerative diseases are associated with metabolic disturbances. Pyruvate dehydrogenase E1 component subunit alpha (PDHA1) is an essential component in the process of glucose metabolism, and its deficiency exists in various diseases such as Alzheimer’s disease, epilepsy, Leigh’s syndrome, and diabetes-associated cognitive decline. However, the exact role of PDHA1 deficiency in neurodegenerative diseases remains to be elucidated. In this study, we explored the effect of PDHA1 deficiency on cognitive function and its molecular mechanism. Methods: A hippocampus-specific Pdha1 knockout (Pdha1-/-) mouse model was established, and behavioral tests were used to evaluate the cognitive function of mice. Transmission electron microscopy (TEM) was performed to observe the morphological changes of the hippocampus. The lactate level in the hippocampus was measured. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting were used to explore the possible mechanism of the effect of PDHA1 on cognition. Results: Pdha1 knockout damaged the spatial memory of mice and led to the ultrastructural disorder of hippocampal neurons. Lactate accumulation and abnormal lactate transport occurred in Pdha1-/- mice, and the cyclic AMP-protein kinase A-cAMP response element-binding protein (cAMP/PKA/CREB) pathway was inhibited. Conclusion: Lactate accumulation caused by PDHA1 deficiency in the hippocampus may impair cognitive function by inhibiting the cAMP/PKA/CREB pathway.